Prevalence and predictors of common psychoactive substances consumption among university students: the role of mental health and academic fields - Espinoza-Turcios, Eleonora; Zambrano, Lysien Ivania; Castro-Ramos, Henry Noel; Sosa-Mendoza, Carlos Antonio; Fuentes-Barahona, Itzel Carolina; Muñoz-Lara, Fausto; Lino de Sousa, Altay Alves (Frontiers in Psychiatry, 2025)
AimThis research focuses on to identify the key predictors of consumption of caffeinated beverages (coffee, tea, and energy drinks) among Honduran university students, focusing on factors such as gender, fatigue, and academic discipline.MethodsA cross-sectional analytical study was conducted at the National Autonomous University of Honduras (UNAH), with students from different programs and academic years enrolled in the second semester of 2023 and the first semester of 2024. The sample consisted of 1,181 students from various faculties, was carried out through surveys in the classroom, before or after classes, ensuring the voluntary participation of students. Participants completed an anonymous Microsoft Forms survey including validated instruments to assess insomnia (severity of insomnia), fatigue (Chalder Fatigue Questionnaire), daytime sleepiness (Epworth Sleepiness Scale), and symptoms of depression, anxiety, and stress (DASS-21). Regression models were used to verify the associated factors with use of consumption of caffeinated beverages in past 6 months and use of illicit drugs at least once in life (Logistic regression) and for the number of different consumptions of caffeinated used in last 6 months, a Poisson model was build.Results83.7% of participants consumed coffee, and 46.8% consumed energy drinks. Men were 3.2 times more likely to consume caffeinated beverages than women. Fatigue was associated with a higher likelihood of consuming energy drinks (OR = 2.10, 95% CI: 1.24–3.55). Economics students were 2.15 times more likely to consume caffeinated beverages, compared to Medical Sciences students (OR = 2.15, 95% CI: 1.06–4.33).ConclusionsFactors such as male sex fatigue, and academic discipline, especially Economics, are significant predictors of caffeinated beverages consumption. Specific interventions are needed to mitigate the negative effects on students mental and physical health.